Lelkiségi mozgalmak a székelyudvarhelyi főesperesi kerületben - Fábián Gabriella; Vallási Néprajzi Konferencia (11.) (2012) (Szeged) (2014)
The study presents briefly three communities of sekler spirituality movement (Catholic Charismatic Renewal, Legion of Mary, St.Monica). The common features of the communities from Sovata and Zetelaka, that they would like to draw the attention to various examples of authentic Christianity with their life examples, like the experience of the Holy Spirit or the traditional Catholic practice of religion inserted in a recent form of the more committed and strict rules. One specific example in the district is the initiative from Székelyudvarhely, the mission for the Christian mothers and families.
Keywords: Bölcsészettudományok; Filozófia, etika és vallástudományok